Highly porous copper oxide sorbent for H2S capture at ambient temperature. (1st December 2017) - Wang, Jian; Wang, Longjiang; Fan, Huiling; Wang, Hui; Hu, Yongfeng; Wang, Zhongde
Abstract: A series of novel highly porous Cu-based sorbents with three-dimensionally ordered macropores structure (3DOM) were synthesized and studied for hydrogen sulfide (H2 S) removal in dynamic conditions at ambient temperature. The fresh, sulfide and regenerated materials were characterized by scanning electron microscopy (SEM), transmission electron microscopy (TEM), nitrogen adsorption studies, X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS), X-ray absorption near edge structures (XANES) spectra. The results show that because of the highly dispersed CuO nanoparticles and large surface area, especially the well-developed macropores, sorbent 3DOM-SC-43 with 3DOM structure presented a considerably high breakthrough H2 S removal capacity from gas streams full of moisture (wet feed) at ambient temperature, almost 6 times than the sample without 3DOM structure, suggesting that 3DOM structure greatly enhanced the H2 S removal ability. The presence of moisture was found to be crucial to keep a high activity for H2 S removal, but the existing H2 S concentration before breakthrough was higher. Modification of sorbent by ammonia vapor deposition method can not only achieve high H2 S removal capacity but also maintain low existing H2 S concentration before breakthrough without the help of moisture. Thermogravimetry coupled with mass spectroscopy (TG-MS) was used to investigate the regeneration of sorbent, showing the regeneration temperature had to be greater than 600 °C considering the decomposition of CuSO4 which is easily formed in air. However, the regenerated CuO/3DOM sorbents did not perform well compared with the fresh CuO/3DOM, but they were still superior to the fresh sorbent without the 3DOM structure.